Complex interplay of Epstein-Barr virus-associated lymphoproliferative disorder, angioimmunoblastic T-cell lymphoma, and paraneoplastic syndromes: A case report - Fiedler, Jacob; Aiello, D.O. Caterina; Jawaid, Tabinda; Anderson, Carinne; Rudinskaya, Alla; Rella, Vincent; West, Jeffrey; Gupta, Gunjan; Fiedler, Paul (Human Pathology Reports, 2025)
We report a diagnostically challenging case of a 66-year-old woman with EBV-positive polymorphic B-cell lymphoproliferative disorder (LPD), angioimmunoblastic T-cell lymphoma (AITL), and endometrial adenocarcinoma. Her initial presentation with RS3PE syndrome and a cutaneous eruption mimicking inflammatory breast carcinoma delayed recognition of underlying lymphoid malignancy. Skin biopsy revealed EBV + LPD, and months later she was diagnosed with AITL via lymph node biopsy. All three neoplasms have been linked to elevated vascular endothelial growth factor (VEGF), suggesting a shared pathogenic pathway. This case underscores the importance of considering EBV + LPD as a potential early marker of TFH lymphoma, especially in immunosenescent patients, and raises the possibility of RS3PE as a paraneoplastic harbinger of VEGF-driven disease. Multidisciplinary evaluation was essential to untangle the overlapping clinical and pathological findings.